Composite Oncocytoma and Papillary Renal Cell Carcinoma of the Kidney Treated by Partial Nephrectomy: A Case Report - Michael S. Floyd; Saqib Javed; Keloth E. Pradeep; Alan R. De Bolla (The Scientific World Journal)
We present the case of a 73-year-old woman who presented with lethargy and a nonproductive cough. Computerised tomography of her abdomen revealed a 38-mm mass in the lower pole of her left kidney. She underwent a partial nephrectomy, with final histopathological analysis confirming the presence of a concomitant oncocytoma and papillary cell carcinoma. To our knowledge, this is the only case report in the world literature describing a papillary renal cell carcinoma within an oncocytoma treated by partial nephrectomy.